PENGARUH MEDIA PEMBELAJARAN MATEMATIKA BERBASIS GAME EDUKASI KAHOOT PADA PEMBELAJARAN TATAP MUKA TERBATAS - Sukiyanto Sukiyanto; Betty Kusumaningrum; Dewi Anggreini; Denik Agustito (Universitas Muhammadiyah Semarang, 2023)
Learning is an activity that is arranged in a planned and systematic manner by involving information and the environment to facilitate students in learning. Efforts that can be made by schools to continue to achieve learning goals during the pandemic, one of which is by implementing limited face-to-face learning. Limited face-to-face learning is learning that implements the Covid-19 prevention process and pays attention to the preparations made by schools before the start of learning, to ensure that learning takes place safely, clearly determining the number of days and hours for the division of limited study groups to be carried out. To see the success of learning mathematics during the learning process. It takes one of the use of learning media that is fun for students. Thus, to overcome this problem, researchers chose to use online-based learning media, namely Kahoot. Kahoot can be accessed at www.kahoot.com which is connected to the internet. During the evaluation at the end of the lesson using the Kahoot application, it can keep students excited and not watching during the learning process. Thus, the purpose of this study is to find out how the use of kahoot learning media in the face-to-face learning process is limited to learning mathematics. While the instruments used in this study were tests, questionnaires and observations. The test questions used in the use of the Kahoot application are 5 questions for each quiz that is carried out 3 times. The test given to students is in the form of multiple-choice questions on the class VII integer material. The questionnaire in this study was in the form of closed questions or statements, aiming to find out the student's response to the evaluation tool that would be given.